Neutrophil-to-lymphocyte ratio in type 2 diabetes patients combined with Lower Extremity Peripheral Artery Disease - Li, Li; Wang, Mengjie; Jia, Ting; Jiang, Xiaowan; Yang, Fan; Wang, Zhongjing; Zhang, Xuyan (Frontiers in Endocrinology, 2024)
Objective This study explored the utility of NLR (neutrophil-to-lymphocyte ratio) as a marker to predict Lower Extremity Peripheral Artery Disease (PAD) in the Chinese population, as well as to assess its consistency and diagnostic value with digital subtraction angiography. Methods Patients were distributed into three groups according to the angiography in lower limb arterial: group L1, plaque with no stenosis; group L2, plaque with luminal stenosis and group L3, total vascular occlusion. Changes in the neutrophil-to-lymphocyte ratio were documented and compared among groups. Results Compared to group L1, NLR was significantly increased in L2 (1.76 vs 2.35, p=0.037) and L3 (1.76 vs 3.60, p<0.001), with a gradual decrease in ABI (Ankle-Brachial Index, 1.11 vs 1.02 vs 0.94, p<0.001). Those older patients with higher prevalence of hypertension (p=0.002), obesity (p=0.032), or reduced high-density lipoprotein cholesterol (p=0.020) were more likely to develop PAD; higher glycosylated hemoglobin (p=0.045), low-density lipoprotein cholesterol (p=0.006), and systolic blood pressure (p<0.001) levels led to a greater tendency to suffer stenosis or even occlusion; the probability of severe stenosis (>70%) increased to 2.075 times for every 1 increase in NLR, while it was 46.8% for every 0.1 increase in ABI. The optimal NLR cut-off value to predict severe stenosis in PAD was 2.73. Receiver operating characteristic curve analysis of the inflammatory biomarkers and severe stenosis prediction displayed an area under the curve of 0.81. Conclusion NLR could serve as a new noninvasive and accurate marker in predicting PAD.